If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 14x + 14 = 6x + -10 Reorder the terms: 14 + 14x = 6x + -10 Reorder the terms: 14 + 14x = -10 + 6x Solving 14 + 14x = -10 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 14 + 14x + -6x = -10 + 6x + -6x Combine like terms: 14x + -6x = 8x 14 + 8x = -10 + 6x + -6x Combine like terms: 6x + -6x = 0 14 + 8x = -10 + 0 14 + 8x = -10 Add '-14' to each side of the equation. 14 + -14 + 8x = -10 + -14 Combine like terms: 14 + -14 = 0 0 + 8x = -10 + -14 8x = -10 + -14 Combine like terms: -10 + -14 = -24 8x = -24 Divide each side by '8'. x = -3 Simplifying x = -3
| h(0)=-2(0)(0)+(0)-5 | | 2.5x+3.5x=180 | | x+y=4.3 | | w-5.16=7.3 | | X^2+2x-10=89 | | h(-1)=-2(-1)(-1)+(-1)-5 | | 15x+5=44x-2 | | D/-1.2=4.8 | | 24=m/3 | | 9=5+a/2 | | 3x^2+64=4x^2+12x | | 11y^2-42y-141=0 | | 4x+24=5x+1 | | 8n+84=84 | | 8x+27=13x | | 5x+6=3x-18 | | -7p-13=-3+2(-4-p) | | -51=3(8+8x)-7(1+x) | | 4y-2x=14 | | s-15=15.50 | | 2/3x=-15 | | A+6.9=4.2 | | -3/4x=-5 | | -9=1/2gw | | 2(3x-4)+8-14= | | 2(3m-6)= | | 9-2x=(-1) | | c=1/2gw | | 16/3] | | g(3)=1/2(3) | | (-6,-8)M=-5/8 | | 1/5d=59 |